From Exclusivism to Openness: Deconstructing the Role of Deaf Individuals as Marriage Witnesses in the Compilation of Islamic Law - Izzuddin, Ahmad; Ni’ami, Mohammad Fauzan; Rouf, Abd.; Irfan, Moh. (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2024)
The role of marriage witnesses for deaf individuals has been a subject of debate among various Islamic schools of thought. The Compilation of Islamic Law (Kompilasi Hukum Islam or KHI), as Indonesia’s codified Islamic jurisprudence, adopts the view of scholars who prohibit deaf individuals from serving as marriage witnesses. This article critically examines the KHI’s stance, arguing that it marginalizes deaf individuals in the marriage process. This study employs a normative approach, utilizing Auda’s maqāṣid al-sharī‘ah concept. The findings reveal that the exclusion of deaf individuals as marriage witnesses stems from the KHI’s restrictive interpretation, which is rooted in classical fiqh. As a legal product influenced by Shafi’i jurisprudence, the KHI maintains the requirement that marriage witnesses must have both auditory and visual capabilities. However, through the principles of openness and purposefulness in Auda’s maqāṣid al-sharī‘ah, this study argues that hearing-impaired individuals possess the necessary qualifications to serve as marriage witnesses. In contemporary society, deaf individuals effectively communicate through various means, including sign language and assistive technologies. Therefore, a legal reinterpretation based on universal Islamic values—particularly those emphasizing equality and justice—is both necessary and justified. [Peran saksi pernikahan bagi individu tunarungu telah menjadi perdebatan di antara berbagai mazhab fikih. Kompilasi Hukum Islam (KHI) mengadopsi pandangan ulama yang melarang individu tunarungu menjadi saksi pernikahan. Artikel ini secara kritis meninjau pandangan KHI, dengan berargumen bahwa ketentuan tersebut (sengaja) meminggirkan individu tunarungu dalam proses pernikahan. Penelitian ini menggunakan pendekatan normatif dengan memanfaatkan kerangka maqāṣid al-sharī‘ah ala Auda. Temuan penelitian ini menunjukkan bahwa eksklusi terhadap individu tunarungu sebagai saksi pernikahan berasal dari interpretasi KHI yang terbatas, yang berakar pada doktrin fikih klasik. Sebagai produk hukum yang banyak dipengaruhi oleh mazhab Syafi’i, KHI menetapkan bahwa saksi pernikahan harus memiliki kemampuan mendengar dan melihat. Namun, melalui prinsip keterbukaan dan ‘kebertujuan’ dalam maqāṣid al-sharī‘ah Auda, penelitian ini berpendapat bahwa individu dengan gangguan pendengaran tetap memenuhi kualifikasi untuk menjadi saksi pernikahan. Dalam masyarakat kontemporer, individu tunarungu dapat berkomunikasi secara efektif melalui berbagai sarana, termasuk bahasa isyarat dan teknologi pembantu. Oleh karena itu, reinterpretasi hukum berdasarkan nilai-nilai universal Islam—khususnya yang menekankan kesetaraan dan keadilan—dapat dibenarkan.]